Public health ethics : key concepts and issues in policy and practice - Dawson, Angus (Cambridge medicine (Series), 2011)
"Public health ethics is a discipline concerned with the health of the public or a population as a whole, rather than focusing on the individual. This book introduces a number of this new field's central concepts and explores the key and controversial issues arising. Topics covered include the nature of public health ethics, the concepts of disease and prevention, risk and precaution, health inequalities and justice, screening, vaccination and disease control, smoking and issues relating to the environment and public health. With insightful contributions from leading experts, Public Health Ethics presents thought-provoking reviews of these topics, at the same time as encouraging and identifying areas for future discussion in this emerging discipline. This is a valuable addition to the library of anyone working in the fields of public health, health policy, ethics, philosophy and social science"--